En-ondulyatorni electron accelerators coaxial type - Куліш, В.В.; Губанов, І.В.; Орлова, О.О.; Сенькович, A.В. (Proceedings of National Aviation University, 2006)
The quantitative and qualitative|quality| analysis of stationary ЕН-accelerator of coaxial type is fulfilled. It is shown that these systems can be used as accelerating system for the relativistic electron beam formation with energy about tens MeV. The project variant of practice realization of EH-accelerator has been proposed on the base of physical analysis.